THE EFFECTS OF VOCABULARY MASTERY AND READING INTEREST TOWARD READING COMPREHENSION (SURVEY AT PRIVATE JUNIOR HIGH SCHOOLS IN WEST JAKARTA) - Sari, Raisa Rahmi; Sumaryoto, Sumaryoto; Supeno, Supeno (INFERENCE: Journal of English Language Teaching, 2024)
The objective of this study is to examine the correlation between students' reading interest and vocabulary mastery as they relate to their reading comprehension. This study utilised a quantitative methodology and a survey as its instrument. The data acquisition methodology involved the utilisation of a questionnaire and a test. The assessment is employed to gather data pertaining to students' reading comprehension and vocabulary mastery, while the questionnaire gathers information regarding students' reading interests. An examination of the hypotheses was conducted using multiple regression analysis. The following are the investigation findings: 1) The combined impact of vocabulary mastery and students' reading interest on students' reading comprehension is statistically significant, as indicated by the Fcount value of 31.628 and the significance level of Sig 0.000, which is less than 0.05. 2) Vocabulary mastery has a substantial impact on the reading comprehension of pupils, as demonstrated by the obtained score and Sig 0.000 < 0.05 and tcount = 5.677. 3) Students' reading comprehension is significantly impacted by their reading interest, as indicated by Sig 0.000 < 0.05 and tcount = 4.492.